Making Meanings: Pupil Talk in Inquiry-Oriented Instruction - Anu Hartikainen (Nordina: Nordic Studies in Science Education, 2012)
This study focuses on seventh-graders’ talk in inquiry-oriented instruction, aiming to describe it and assess its meaning. The study was carried out in the framework of the sociocultural theory, where learning is seen as a social activity and talk is therefore assigned an important role in any analysis learning. The data were collected in situations where the pupils were studying biology in inquiryoriented instruction. The data comprise 10 hours of recorded discussions among a group of pupils, which were analyzed by means of a discourse analysis focusing on the construction of the pupils’ meaning-making processes. The meaning-making processes were generated by means of rhetorical and dialogical speaking strategies. The results indicate that only dialogical strategies led to intersubjectivity and collaborative knowledge-construction. The findings also show that talk is a principal tool for creating a frame for pupils’ collaboration and learning. It seems that in order to derive the most benefit for their learning from inquiry-oriented activities in the science classroom, pupils need to be taught how to talk together.